The AIP (aryl hydrocarbon receptor-interacting protein) gene and its relation to the pathogenesis of pituitary adenomas - Lloyd, C; Grossman, A (Humana Press Inc., 2014)
Pituitary adenomas are monoclonal neoplasms that may secrete excessive quantities of their endogenous hormones, or may not be associated with any obvious syndrome, in which case they are known as non-functioning pituitary adenomas. Around 2 % have been said to occur in a familial setting, in the absence of any other tumor, now described as familial isolated pituitary adenomas (FIPA). Some 15-30 % of such families harbor inactivating germ-line mutations in the aryl hydrocarbon receptor-interacting protein (AIP) gene, along with 20 % of pediatric seemingly sporadic cases. AIP mutants are referred to as having pituitary adenoma predisposition, and present with early onset, aggressive macroadenomas, most of which secrete somatotropin. Evidence from transfection studies implies that AIP acts as a tumor suppressor; although whether this is mediated through an interaction with the aryl hydrocarbon receptor, phosphodiesterases, or with cell cycle regulators such as survivin or RET remains controversial. However, at present an interaction with the cyclic AMP pathway seems most plausible. Recently, evidence has shown that AIP may act at the cell surface, causing changes in integrin function. The presence of AIP mutations in a significant proportion of FIPA families as well as in apparently sporadic cases, particularly in young patients, suggests a need to screen such patients for AIP mutations to enable better clinical management. However, the absence of AIP mutations in over half of such cases highlights the need to search for further gene mutations. © 2013 Springer Science+Business Media.